Microleakage evaluation of two types of pit and fissure sealants using two different methods, (in vitro study) (Mustansiria Dental Journal, 2018)
Background: Clinical preventive procedures must be done after careful assessment;one of the major risk factor is the occlusal morphology of the posterior teeth. Thesecaries free fissures must be sealed. This in vitro study evaluated the microleakage oftwo types of sealant materials (unfilled resin and flowable composite) on enamelsurfaces prepared using two methods (acid etching with enameloplasty and acidetching alone).Material and methods: Thirty two extracted human third molar were selected andrandomly assigned in to 4 groups of eight teeth each; group A, the occlusal surfaces ofteeth were acid etched ,then sealed with concise white sealant; group B, they wereacid etched then sealed with wave mv flowable composite ;group C, they wereprepared with bur ,acid etched ,then sealed with concise white sealant ;group D, theywere prepared by bur, acid etched, then sealed with wave mv flowable composite. Thesealed surfaces were stored for seven days in distilled water, then specimens werethermocycled 500 cycles, immersed 24 hours in a 2% buffered methylene blue dye,then sectioned and analyzed for leakage under a stereo microscope. Chi-square testwas performed to test the differences of leakage among the four groups.Results: The results showed that there was no significant difference (p>0.05) inmicroleakage for the same material with and without bur preparation. Concise whitesealant produced significantly (p